Rationally Armoring PtCu Alloy with Metal‐Organic Frameworks as Highly Selective Nonenzyme Electrochemical Sensor. Issue 23 (8th October 2018) - Chen, Luning; Wang, Tao; Xue, Yakun; Zhou, Xi; Zhou, Jinhong; Cheng, Xiqing; Xie, Zhaoxiong; Kuang, Qin; Zheng, Lansun
Abstract: The nonenzymatic electrochemical sensors based on nanomaterials recently have attracted increasing attention because of the limitations of natural enzyme‐based sensors in stability and reproducibility. However, traditional nonenzymatic electrochemical sensors suffer from poor selectivity and antiinterference capacity in spite of high activity and stability. Herein, a kind of well‐designed nonenzymatic electrochemical sensor with a PtCu@metal organic frameworks (MOFs)/C configuration is successfully constructed. In this sensor configuration, PtCu alloy nanoparticles as H2 O2 ‐active centers, which are preloaded on an electroconductive support, are armored with a Cu‐based MOF shell via a self‐sacrificial template route to form a semisurrounding structure. Thanks to the synergy between the MOF shells and the well‐consolidated PtCu/electroconductive support interface, this nonenzymatic sensor not only exhibits superior selectivity and antiinterference capacity toward the detection of H2 O2, but also illustrates its great potential in real biological systems (e.g., living tumor cells). The present work greatly deepens the understanding of the role of MOF shells in improving the sensing performance of nonenzymatic electrochemical sensors based on MOF composites. More importantly, these findings provide new design views for the rational construction of high‐performance MOF‐based composites. Abstract : Traditional nonenzymatic electrochemical sensors suffer from poor selectivity and antiinterference capacity in spite of high activity and stability. Herein, a kind of well‐designed nonenzymatic electrochemical sensor with a PtCu@MOFs/C configuration is successfully constructed. Thanks to the synergy between the MOF shells and well‐consolidated PtCu/electroconductive support interface, this sensor exhibits superior selectivity and antiinterference capacity toward the detection of H2 O2 .